ANALISIS KEUNTUNGAN DAN SKALA USAHA PETERNAKAN SAPI PERAH RAKYAT DI KOTA SEMARANG - Agus Riyanto; Purbayu Budi Santosa (Universitas Diponegoro, 2013)
Dairy farm businesses have considerable market potential in urban areas and one of Semarang because it has facilities and adequate transportation infrastructure so that the milk is raw material can be reached by the end consumer level. Dairy farm business people can be developed either through: (1) facilities and prasrana subsystem, (2) cultivation, (3) post-harvest, (4) processing and marketing efforts. This study aims to determine how much influence the cost of green feed cost, concentrate feed costm, labor cost, cost of medicine, capital, training and experience to benefit farmers and determine the condition of scale and also the maximum profit from dairy cattle business people in the City Semarang. The research method used Unit Price Output Function (UOP) using SPSS 17 of data processing. The results showed that the variabel cost of concentrate feed, the cost of medicine, cost of capital and labor jointly significant advantages both for the 0,01 and 0,05. R2 value of 0,634 which 63,4 percent of these variables can be explained while the independent variables by other dependent. Dairy farm business people in the city of Semarang has not reached the maximum profit and the condition of its business scale also leads to decreasing retrun to scale.